Latrine Utilization and Associated Factors Among Rural Households in Southwest Ethiopia: Risk, Attitude, Norms, Ability, and Self-Regulation Behavioral Model - Eyasu Bamlaku Golla; Temesgen Bati Gelgelu; Mikael Deguale Adane; Tesfaye Tsegaye Giday; Abiyot Wolie Asres; Takele Tadesse Adafrie (SAGE Publishing, 2023)
Background: Consistent latrine utilization remains a challenge in most rural areas of poor and middle-income countries including Ethiopia. Therefore; the objective of this study was to determine the magnitude of latrine utilization and its associated factors among rural households in open defecation-free declared (ODF) and non-ODF kebeles, Southwest Ethiopia, 2022. Methods: A community-based comparative cross sectional study design was employed from May 16 to June 14, 2022 among 682 (341 ODF and 341 non-ODF) rural households which were selected by multistage systematic random sampling technique. Data were collected by face to face using a pretested structured questionnaire and an observational checklist through Open data kit. SPSS version 26 was used to analysis the data and separate logistic regression models; ODF and non-ODF were run to identify the associated factors. P -values <.05 with 95% CI were set as statistical significant. Result: The overall magnitude of latrine utilization in the study area was 67.1% (95% CI: 63.71, 70.49). Latrine utilization was higher in ODF declared households (71.6%) than in non-ODF households (62.5%). In ODF; Graduated as model households [AOR = 5.1, 95% CI: 2.14, 12.84], visited by health extension works (HEWs) [AOR = 3.5, 95% CI: 1.67, 7.25], and latrine with privacy [AOR = 3.0, 95% CI: 1.37, 6.65] and also in non-ODF; households visited by HEWs [AOR = 2.9, 95% CI: 1.34, 6.06], latrine with privacy [AOR = 2.5, 95% CI: 1.24, 5.07], positive attitude [AOR = 3.2, 95% CI: 1.52, 6.59], and descriptive norm [AOR = 2.7, 95% CI: 1.27, 5.53] were significantly associated with latrine utilization. Conclusion: This study found that rural households declared as ODF utilize their latrine higher than non-ODF. Constructing latrine without privacy, lack of follow up, Attitude and societal norms were factors that limited the utilization of latrine and the sustainability of ODF. Therefore, health extension follow-up, latrine construction with privacy, normative and persuasive behavior change approach should be encouraged.